Malignant retroperitoneal teratoma in a young girl: a rare case report - Patwardhan, Maneesha Anil; Shinde, Raju Kamlakar; Golhar, Keshao Bhagwant; Rathod, Vishal; Amle, Gaurav; Jauhari, Abhinav (International Journal of Research in Medical Sciences, 2017)
Of all primary retroperitoneal teratomas, less than four percent occur in children and 90% are benign. Here we report a case of malignant retroperitoneal teratoma (dermoid) in a 15 year old girl who presented to our hospital - Acharya Vinoba Bhave Rural Hospital (AVBRH). She presented with a tender, large, irregular mass with variegated consistency in the entire left side of abdomen crossing midline. Ultrasound of abdomen suggested a complex intra-abdominal mass with septations and lobulations. It was not feasible to use other imaging modalities for evaluation due to poor socio-economic status and illiteracy. Patient underwent exploratory laparotomy with tumor resection along with left kidney and part of the descending colon which was densely adhered to tumor. Histopathological examination of tumor was suggestive of immature teratoma. Post operative recovery was uneventful and patient was discharged from the institution. Tissue adherence which can be observed in both benign and malignant form of teratomas, requires extended surgery for removal of adhered organ for the completeness of surgery and good prognosis.